A conceptual model of stress and psychological resources in return migration. - Ozola-Cīrule, Iveta; Martinsone, Baiba (International Journal of Intercultural Relations, 2026)
This study develops a qualitative, empirically grounded conceptual model that links stress factors to psychological resources in the context of return migration. In-depth interviews with 21 voluntary return migrants in Latvia (with long-term experience abroad) and a separate focus group with five participants were analysed using grounded theory. Analysis identified the mobilisation of buffering mechanisms as the core category, conceptualising return as a dynamic process structured into three sequential phases: triggers of return stress (pre-return context and external conditions), psychological tension and vulnerability, and resource mobilisation and coping (perceived social support and psychological resources). The model indicates that the evaluation of stress factors and psychological resources, and subsequent coping, are not limited to the post-return period; for many participants, the pre-return phase was described as emotionally intense and consequential for later adjustment. The findings highlight the critical role of psychological resources, such as cognitive flexibility, self-efficacy, positive reframing, proactive behaviour, identity integration, intercultural competence, and a long-term perspective, in managing return-related demands. The study offers a coherent framework for organising previously fragmented topics and provides an analytical tool for future research and practice. Implications include strengthening information and support before return, addressing needs in family, school, and work settings, and designing interventions that recognise and develop psychological resources alongside structural and institutional supports. • The model frames return migration as a three-phase process of self-regulation. • The mobilisation of buffering mechanisms acts as the core category of adaptation. • The pre-return phase involves anticipatory stress, shaping subsequent adjustment. • Conceptual links connect external structural demands to internal human adaptation. • Psychological resources actively regulate post-return emotional ambivalence.